2021
DOI: 10.1002/ente.202100092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endplate Assembly on Cold Start Performance of Proton Exchange Membrane Fuel Cell Stacks

Abstract: Figure 1. a) Schematic diagram of a PEMFC stack and b) mesh of the computed geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…They found the stack had a better performance than the single cell in the cold start, the middle cell in the stack had better performance than the end cell, and the consistency of stack became worse after the cold start failed. Wei et al 30 established a three-dimensional multi-phase transient model of the stack, and studied the effects of the end plate on the performance of the stack during the cold start process by analyzing the distribution of water, ice, the current density and the temperature in the stack. They found that the end plate had a great influence on the stack under the condition of −30°C, which directly causing the end plate side cells to be completely blocked by ice.…”
mentioning
confidence: 99%
“…They found the stack had a better performance than the single cell in the cold start, the middle cell in the stack had better performance than the end cell, and the consistency of stack became worse after the cold start failed. Wei et al 30 established a three-dimensional multi-phase transient model of the stack, and studied the effects of the end plate on the performance of the stack during the cold start process by analyzing the distribution of water, ice, the current density and the temperature in the stack. They found that the end plate had a great influence on the stack under the condition of −30°C, which directly causing the end plate side cells to be completely blocked by ice.…”
mentioning
confidence: 99%
“…The problem with cold starts occurs in the system when recommending accurately becomes challenging with new users who lack rating data or have sparse data. This problem cannot be ignored during operation, making it a difficult issue to address [21] . The issue of data sparsity is predominantly a result of the increasing number of users and data stored over time.…”
Section: A Cf-based Book Recommendation Model For University Librariesmentioning
confidence: 99%
“…The present 3D PEMFC model resorts to fuel cell computational dynamics and is based on our previous work. [ 35 ] It has the capability of analyzing the coupled transport and reaction processes and, to understand the possibility of operating without external humidification of the reactant gases, the dry operation condition. [ 36 ] It has been shown that only a small amount of liquid exists near the outlet of the channel under low humidification operation.…”
Section: Model Descriptionmentioning
confidence: 99%